Karst Geomorphology and Hydrogeology of the Northeastern Mackenzie Mountains, District of Mackenzie, N.W.T. - Hamilton, James P. (My University, 1995)
This thesis describes the geomorphology and hydrogeology of karst systems in portions of the northeastern Canyon Ranges of the Mackenzie Mountains and the Norman Range of the Franklin Mountains, N.W.T. In the region, mean annual temperatures are -6 to -8°C, total annual precipitation is 325 to 500 mm, and permafrost has a widespread to continuous distribution. The area was glaciated in the Late Wisconsinan by the Laurentide Ice Sheet.
The Canyon Ranges and Norman Range are composed of a sequence of faulted and folded miogeoclinal sedimentary rocks that span the Proterozoic to Eocene. The geology is reviewed with an emphasis on strata that display karst. Included are several dolomite and limestone formations, two of which are interbedded with evaporites in the subsurface. The principal groundwater aquifer is the Lower Devonian Bear Rock Formation. In subcrop, the Bear Rock Formation is dolomite and anhydrite, outcrops are massive calcareous solution breccias. This is the primary karst rock.
The regional distribution and range of karst landforms and drainage systems are described. Detailed mapping is presented from four field sites. These data were collected from aerial photography and ground surveys. The karst has examples of pavement, single and compound dolines, subsidence troughs, polje,sinking streams and lakes, and spring deposits. The main types of depressions are subsidence and collapse dolines. Doline density is highest on the Bear Rock Formation. Surficial karst is absent or less frequent in the zone of continuous permafrost or outside the glacial limit.
At the field sites, water samples were collected at recharge and discharge locations. Samples were analyzed for a full range of ionic constituents and many for natural isotopes. In addition, several springs were monitored continuously for discharge, temperature, and conductivity. Dye tracing established linkages between recharge and discharge at some sites. These data are summarized for each site, as is the role of permafrost in site hydrology.
The relationships between geological structure, topography, and groundwater systems are described. Conduit aquifers are present in both dolomite and limestone. These systems are characterized by discharge waters of low hardness and dissolved ion content. Aquifers in the Bear Rock Formation have a mixed flow regime and often have highly mineralized discharge. At the principal field site, there was a time lag of 40 to 60 days between infiltration and discharge in this unit. At a second site, flow through times were on the order of years. Variability in these systems is attributed to bedrock properties and boundary conditions.
Preliminary rates of denudation are calculated from the available hydrochemical data. Total solutional denudation at the primary field site is approximately 45 m3 km-2 a-1 (mm ka-l ). The majority is attributed to the subsurface dissolution of halite and anhydrite. The predominance of subsurface dissolution is linked to the high frequency of collapse and subsidence dolines and depressions.
The karst features and drainage systems of the northern Mackenzie Mountains date to the Tertiary. Glaciation has had a stimulative effect on karst development through the subglacial degradation of permafrost and the altering of boundary conditions by canyon incision.
Keywords: Geography; karst systems; geomorphology; hydrogeology